2020
DOI: 10.1002/mp.14347
|View full text |Cite
|
Sign up to set email alerts
|

Cone‐beam CT‐derived relative stopping power map generation via deep learning for proton radiotherapy

Abstract: In intensity-modulated proton therapy (IMPT), protons are used to deliver highly conformal dose distributions, targeting tumors, and sparing organs-at-risk. However, due to uncertainties in both patient setup and relative stopping power (RSP) calculation, margins are added to the treatment volume during treatment planning, leading to higher doses to normal tissues. Cone-beam computed tomography (CBCT) images are taken daily before treatment; however, the poor image quality of CBCT limits the use of these image… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 51 publications
1
18
0
Order By: Relevance
“…For proton RT, the setup accuracy and dose calculation are even more relevant to avoid RS errors that could jeopardise the benefit of treatment 63 . Because there is an intrinsic error in converting HU to relative proton stopping power, 178 it has been shown that DL methods can translate CBCT directly to stopping power 179 . This approach has not been covered in this review, but it is an exciting approach that will probably lead to further investigations.Interestingly, increasing the quality of CBCT can be tackled not only as an image‐to‐image translation problem but also as an inverse problem, that is, from a reconstruction perspective.…”
Section: Discussionmentioning
confidence: 99%
“…For proton RT, the setup accuracy and dose calculation are even more relevant to avoid RS errors that could jeopardise the benefit of treatment 63 . Because there is an intrinsic error in converting HU to relative proton stopping power, 178 it has been shown that DL methods can translate CBCT directly to stopping power 179 . This approach has not been covered in this review, but it is an exciting approach that will probably lead to further investigations.Interestingly, increasing the quality of CBCT can be tackled not only as an image‐to‐image translation problem but also as an inverse problem, that is, from a reconstruction perspective.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with what has been reported in adult head and neck patients (average passing rate of 94% for 3%/3 mm) who were originally treated with photons and were retrospectively replanned for proton therapy. 19 It is interesting to note that the sites with the lowest pass rates corresponded to the mediastinum (87%) and lung (90%). This may reflect the limitations of deformable registration, where the displacement between ribs and lung may not be accurately modeled without specialized algorithms.…”
Section: Discussionmentioning
confidence: 97%
“…presented a single detector, multi-energy proton radiography system which relied on artificial intelligence to filter out proton scatter ( 198 ). In addition, multiple studies have been reported which utilize deep learning as a tool to facilitate accurate proton dose calculation from daily CBCT images ( 121 , 199 201 ). Elmahdy et al.…”
Section: Future Technologiesmentioning
confidence: 99%
“…Van der Heyden et al presented a single detector, multi-energy proton radiography system which relied on artificial intelligence to filter out proton scatter (198). In addition, multiple studies have been reported which utilize deep learning as a tool to facilitate accurate proton dose calculation from daily CBCT images (121,(199)(200)(201). Elmahdy et al also reported on a convolutional neural network (CNN)-based model for robust, automatic contour propagation in prostate cancer for online adaptive proton therapy (202).…”
Section: Artificial Intelligencementioning
confidence: 99%